Barrier To Entry Dalam Kebijakan Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal Menurut Putusan Dispute Settlement Body Nomor 484 Tentang Kasus Impor Daging Ayam Dan Olahan Daging Ayam Oleh Brazil - Ahmad Farhan Hadad; Hasanudin Hasanudin; Indra Rahmatullah (JOURNAL of LEGAL RESEARCH, 2020)
The main problem in this article is how the implementation of halal product guarantees creates a barrier to entry based on Law Number 33 of 2014 concerning Halal Product Guarantee according to the Dispute Settlement Body Decision number 484. The research method uses a juridical normative approach. Juridical normative research has two sources of law, namely primary and secondary sources of law. Primary sources of law refer to the Dispute Settlement Body Decision Number 484 and Law Number 33 of 2014 concerning Halal Product Guarantee. The secondary source of law refers to the book by Huala Adolf entitled International Trade Law. The results of the study indicate that the Dispute Settlement Body decision has binding power for the Indonesian state because Indonesia is part of the WTO. This decision also gave the impact of creating uncertainty in the law, especially regarding the Halal Product Guarantee. The efforts of the Indonesian state to protect the Halal Product Guarantee by making an appeal to the Dispute Settlement Body, although the results are still not in accordance with what Indonesia wants.